A Beyond Social Darwinism: Political Symbiogenesis as a New Paradigm in Institutional Theory - mehdi Bideli (POLTRANS: Journal of Politics and Social Transformation, 2026)
This article introduces the concept of political symbiogenesis as an interdisciplinary framework that, drawing inspiration from evolutionary biology, views the transformation of political institutions not merely as a result of competition and elimination, but as a consequence of sustained symbiosis, mutual interdependence, and increasing complexity. In biology, symbiogenesis emphasizes the role of symbiotic relationships in the emergence of fundamental evolutionary innovations. Critically distancing itself from social Darwinism, this article argues that certain political transformations can also be understood in terms of institutional symbiosis a process in which distinct actors and institutions, through stable relationships of mutual interdependence, transform into newer, more complex orders. The necessity of this new concept, rather than merely extending existing theories, arises from the inability of competition-centric frameworks to explain complex contemporary phenomena such as network governance, federalism, and the coexistence of heterogeneous identity groups. Methodologically, this article is a theoretical-conceptual study that relies on conceptual analysis, interdisciplinary comparison, and critical reinterpretation of the literature. The theoretical findings suggest that political symbiogenesis can serve as a generative analytical concept for understanding these phenomena without being reduced to biological determinism or simplistic analogies. The value of this concept lies in its vision of politics not merely as an arena of conflict, but as a context for the formation of newer, more complex units.